(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Phyllanthus niruri leaves and Sapindus mukorossi fruits have been traditionally used as anti-inflammatory, anti-pyretic and analgesic, anti-fungal, anti-microbial, anti-bacterial and antiparasitic, expectorant, emetic, anti-cancer, mood elevator, and as hepatoprotective. The present study was designed to investigate the anti-stress activity of combined extract of P. niruri leaves and S. mukorossi fruits employing various activities using experimental animals. Rats and Mice were separated into five groups, consisting of six animals each. Methanolic extract of P. niruri leaves (MEPNL), aqueous extract of S. mukorossi fruit (AESMF), and combined extract (MEPNL+AESMF) were prepared and anti-stress activity was investigated by Anoxia induced stress in mice, Immobilization stress in rats, and Swimming endurance test in mice. Combined extract (400 mg/kg, p.o.) exhibited remarkable effect as it delayed onset of convulsion time in anoxia stress model when equated to individual extracts. In swimming endurance test, combined extract (400 mg/kg, p.o.) displayed significant effect as it enhanced swimming time in mice when compared to MEPNL (400 mg/kg, p.o) and AESMF (400 mg/kg, p.o). Combined extract has remarkably reduced the serum levels of glucose, triglycerides, cholesterol, blood urea nitrogen, and cortisol in rats as equated to control. Combination of extracts has produced remarkable and protective effects on organs such as liver, adrenal gland, spleen, and testes. Present study showed that the combined extract of P. niruri leaves and S. mukorossi fruits possessed significant anti-stress action, which was found to be higher than the individual extracts. This indicates the synergistic anti-stress efficacy of the combination of extracts. However, future studies are essential to focus on the cellular mechanism of quantitative phytochemical constituents and ascertain the precise mode of action involved in its anti-stress property.